2014
DOI: 10.1002/jca.21342
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic plasma exchange and immunosuppressive therapy in a patient with anti-GAD antibody-related epilepsy: Quantification of the antibody response

Abstract: Antibodies to glutamic acid decarboxylase (GAD) have been associated with a host of neurological disorders including stiff person syndrome, cerebellar ataxia, limbic encephalitis, and epilepsy. Whether anti-GAD antibodies have an etiological role in these neurological disorders or simply serve as disease markers is unclear. Here, we report a case of a patient with recurrent seizures, poorly responsive to conventional treatment, associated with anti-GAD antibodies. The patient was experiencing near daily seizur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…A number of previous case reports or small patient series on therapy outcome of GAD-TLE using immunotherapy produced inconsistent results [3,4,[30][31][32][33][34][35]. In a recently published study regarding seizure outcome of patients with autoimmune epilepsies, four GAD-TLE patients were included: two of them had a favourable outcome under immunotherapy with IVIG and MP gaining seizure-freedom for a period of 6-18 months [36].…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous case reports or small patient series on therapy outcome of GAD-TLE using immunotherapy produced inconsistent results [3,4,[30][31][32][33][34][35]. In a recently published study regarding seizure outcome of patients with autoimmune epilepsies, four GAD-TLE patients were included: two of them had a favourable outcome under immunotherapy with IVIG and MP gaining seizure-freedom for a period of 6-18 months [36].…”
Section: Discussionmentioning
confidence: 99%
“…Although there were conflicting results regarding immunotherapy responses, the successful treatment of refractory epilepsy after immunotherapy has been reported in previous cases (Farooqi et al, 2015;Kanter et al, 2008). Furthermore, cortical GABA levels were reported to decrease in patients with temporal lobe epilepsy and GAD-Abs, but there was no difference in a composite measure of glutamate and glutamine (Stagg et al, 2010).…”
Section: Discussionmentioning
confidence: 87%
“…The characteristics of these epileptic seizures were de jà vu, absence and automatism. Farooqi et al [72] reported that a 23-year-old female patient who had a 4-year history of epilepsy in the form of generalized tonic-clonic seizures was hospitalized for an increased frequency of seizures (from once a week to once a day). These seizures predominantly occurred during the night and lasted 1-2 min.…”
Section: Seizure Characteristics and Prognosis Of Anti-gad Antibody-assmentioning
confidence: 98%